KAWASAN INDUSTRI BERBASIS EKOLOGI - Sujiman Sujiman (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2016)
This study aims to analyze alternative priorities of the development strategy of Ecology-Based Industrial Zone (EBIZ) and a key of programe in the development strategy of the EBIZ concept. Data analysis was performed using the method of system integration experts, which AHP and ISM. Data collected in the form of secondary data (real data and hypothetical data), both quantitative and qualitative where data collection was done by using survey techniques. The manufacturing industry is one sector the largest foreign exchange earner for the national economy. However, the sector is under pressure due to the high contribution to the reduction of environmental quality and relatively high dependence on natural resources. During the manufacturing industry see the waste that it generates as a burden which if addressed fully will be able to reduce the competitiveness of the industry. Facing the challenges of the 21st century industry, came the concept of "industrial ecology," which is a concept that aims to implement a system of ecological systems in the industry. This concept can be applied successfully in groups of manufacturing industries located in an industrial area that is known as "eco-industrial parks." The result is a top priority for the development strategy of Region-Based Industrial Ecology is the implementation of an integrated Ecology-Based Industrial Zone by industrial relocation to the industrial area. The success of the effort to implement integrated Ecology-Based Industrial Zone by relocation of industries to the industrial area should be supported by several factors, of which the foremost is the consistency of legislation